Topical sirolimus for the treatment of verrucous epidermal nevus associated with an HRAS mosaic mutation: a case report - Qiu-ju Wei; Wan-yan Xiang; Wen-jun Zheng; Qiu-ju Li (Frontiers in Medicine, 2026)
Introduction Verrucous epidermal nevus is a benign epidermal hamartoma associated with somatic mosaic mutations, which shows poor response to conventional therapies and has a high risk of recurrence. To date, there are no standardized treatment guidelines for this condition. In recent years, targeted treatments for specific gene mutations have provided new directions for the clinical management of this disease. Case report We report a case of a 13-year-old child with verrucous epidermal nevus in whom genetic testing revealed an HRAS mosaic mutation. The child showed poor response to conventional treatments, including surgical excision, topical retinoic acid cream, and oral acitretin. However, after treatment with topical 0.5% (w/w) sirolimus ointment, the child’s skin lesions showed reduced area, thinning, improved pigmentation, and decreased roughness, and no local or systemic adverse reactions were observed during the 6-month treatment period. Conclusion This case suggests that topical sirolimus may represent a potentially effective therapeutic option for patients with verrucous epidermal nevus who are refractory to conventional therapy.